Scaling Up Sweetpotato through Agriculture and Nutrition (SUSTAIN) 2013‐2019. Final report. - International Potato Center (International Potato Center, 2019)
The Scaling Up Sweetpotato through Agriculture and Nutrition (SUSTAIN) project (2013–2019) aimed to improve the diets of at least 2.3 million households with children under 5 years of age in Africa and South Asia through biofortified (vitamin A‐rich) orange‐fleshed sweetpotato (OFSP). SUSTAIN applied integrated agriculture and nutrition interventions to scale up the production and consumption of OFSP and assessed the effectiveness of different delivery approaches for reaching its target population. It focused on Kenya, Malawi, Mozambique, and Rwanda, with additional activities in Bangladesh and Tanzania. It was led by the International Potato Center (CIP) working in partnership with national agriculture research institutions, health services, civil society organizations, and private sector partners. SUSTAIN resulted in more than 2.3 million farming households with children under 5 years of age producing and consuming OFSP. It also reached over two million caregivers through nutrition education and training to improve their capacity for OFSP use for household nutrition, in particular feeding young children. These household numbers include those that were directly engaged in SUSTAIN’s activities and those that indirectly accessed OFSP and nutrition knowledge through farmer‐to‐farmer diffusion and related partner initiatives using OFSP technologies and behavior change modules developed by SUSTAIN.